Land consolidation cases relating to grazing arrangements - Per Kåre Sky; Helén Elisabeth Elvestad (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2021)
Land consolidation courts deal with cases where the relationship between holders of grazing rights needs be regulated, but also where the rights holders are competing with other potential land uses, such as building holiday cabins, forestry, hunting, etc. These cases are governed by the provisions of sections 3-8 and 3-10 of the Land Consolidation Act. We have analysed 20 grazing arrangements, based on the following criteria: duration of the case; substantive and geographic limits to the case, and how the parties' claims influenced the final shared use arrangement; need for expert advice; the parties' counsels; clarification of the legal basis and the need for dispute resolution; use of tools provided by the Land Consolidation Act; interconnection with other rights; in cases dealing with several types of land use – did the land consolidation court establish several associations or a single association; and issues arising in established grazing arrangements and associations. We provide examples of the material considerations, both general and detailed, that were given weight when drawing up the rules on grazing.
Keywords: K11; Q15; 330; Land consolidation; Grazing arrangements; Rural areas; Norway